2014
DOI: 10.1016/j.atherosclerosis.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone mineral density in the inverse relationship between body size and aortic calcification: Results from the Baltimore Longitudinal Study of Aging

Abstract: OBJECTIVE There is a J-shaped relationship between body mass index (BMI) and cardiovascular outcomes in elderly patients (obesity paradox). Whether low BMI correlates with aortic calcification (AC) and whether this association is accounted for by bone demineralization is uncertain. METHODS Presence of AC was evaluated in 687 community-dwelling individuals (49% male, mean age 67±13 years) using CT images of the thoracic, upper and lower abdominal aorta, and scored from 0 to 3 according to number of sites that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The increase of carotid wall thickness is at the basis of arterial stiffening and loss of elasticity [22,23]. Arterial stiffening is one of the hallmarks of vascular aging, and is an important risk factor for cardiovascular morbidity and mortality [24][25][26][27][28]. Recent evidences suggest that arterial stiffness accelerates within 1 year of the final menstrual period [29]; therefore, subclinical atherosclerosis is progressive and aggressive in postmenopausal women; thus, increasing their cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of carotid wall thickness is at the basis of arterial stiffening and loss of elasticity [22,23]. Arterial stiffening is one of the hallmarks of vascular aging, and is an important risk factor for cardiovascular morbidity and mortality [24][25][26][27][28]. Recent evidences suggest that arterial stiffness accelerates within 1 year of the final menstrual period [29]; therefore, subclinical atherosclerosis is progressive and aggressive in postmenopausal women; thus, increasing their cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…The process of transdifferentiation of VSMCs to the osteogenic phenotype plays a crucial role in arterial calcification 36 . Epidemiological studies have shown that the incidence of aortic calcification is intimately related to low bone mineral density in postmenopausal women; this phenomenon is known as the calcification paradox 37 , 38 . These studies suggest that oestrogen plays an important role in the development of arterial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, clinical studies demonstrated that Mg therapy significantly suppressed PTH secretion in CKD, which in turn prevented the development of uremic bone diseases and AC (41,62). Moreover, low BMI was associated with increased AC, possibly through calcium mobilization from bone, resulting in decreased bone mineral density (10).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%